Synergistic Catalysis by “Polymeric Microzymes and Inorganic Nanozymes”: The 1+1>2 Effect for Intramolecular Cyclization of Peptides - Chen, Zhiliang; Sellergren, Börje; Shen, Xiantao (Frontiers in Chemistry, 2017)
In this work, we developed an efficient “molecularly imprinted polymer microzymes and inorganic magnetic nanozymes” synergistic catalysis strategy for the formation of disulfide bonds in peptides. The polymeric microzymes showed excellent selectivity toward the template peptide as well as the main reactant (linear peptide), and the Fe3O4 magnetic nanoparticle (MNP) nanozymes inhibited the intermolecular reaction during the formation of disulfide bonds in peptides. As a result, the integration of the two different artificial enzymes in one process facilitates the intramolecular cyclization in high product yields (59.3%) with excellent selectivity. Mechanism study indicates the synergistic effect was occurred by using a “reversed solid phase synthesis” strategy with an enhanced shift of reaction balance to product generation. We believe the synergistic catalysis by “polymeric microzymes and inorganic nanozymes” presented in the present work may open new opportunities in creation of multifunctional enzyme mimics for sensing, imaging, and drug delivery.